Studi Fenomenologi Pola Komunikasi Konselor Dan Residen Di Lembaga Rehabilitasi Pencegahan Penyalahgunaan Narkoba Bhayangkara Indonesia Di Kota Medan - Ulfah Aulia Batubara; Nadra Ideyani Vita; Rehia K.I. Barus (Universitas Medan Area, 2022)
This thesis aims to know the form of communication patterns of counselors and residents from a phenomenological point of view that occurs in the Rehabilitation Institute for Drug Abuse in Bhayangkara Indonesia at Medan City. Effective communication patterns are known as two-way communication and the individuals who get involved are able to mutually interpret the contents with the main and expected goals. This study is taken from resident's experience when they communicating with counselors and how the surrounds condition can affect the formation of meaning when that communication occurs. To obtain data in this study, it has been done by interviewing respondents and informants and studies of related documents. The communication pattern that occurs between counselors and residents at the Rehabilitation Institute for Drug Abuse in Indonesia at Medan City forms a circular two-way communication patterns while in the process both of communicators and communicants involved are able to exchange functions and roles by chances. The narcotics resident who was motivated by various reasons when he entered rehabilitation created a blocking system to not opened himself off from his counselor. The conclusion is known that two-way communication between it cannot be separated from self-disclosure to open his ownself.